The beingness of Ojo’Ochamachala and the existential proofs of god in Igala metaphysics (2023)
The subject matter of metaphysics revolves around different aspects of reality, including man, nature, the cosmos, human mind and God’s existence among others. The nature and reality of the Supreme being like other conjectural problems of metaphysics have polarized scholars as a major concern over the years. On the one hand, it is asserted that no rational account or argument for the existence of God should even be attempted because of the dearth of empirical proofs. On the other hand, others posit that thanks to their firsthand encounters with various manifestations of extraterrestrial life, there are valid ways to demonstrate the existence of God. This paper conceptually dwells on beingness of Ojo’Ochamachala, the Supreme Being in Igala land. It sets out to answer the following research questions; What is understood as the beingness of Ojo’Ochamachala in Igala land? How is the metaphysical existence of God seen in Igala traditional System? What can be characterized as beingness of the Supreme Being in the Igala context? What are expressions of interpretative divination of God in Igala metaphysics? These questions will be answered with the view to providing existential proofs of God in Igala metaphysics